GUI for PC auto-shutdown - Mohd. Liakot , Ali; Islam, Md. Rafiqul; A. Siti , Anom; M.Y. Nurul , Amziah (Elsevier, 2007)
Computer is a part and parcel of our daily life. It is being widely used at homes, offices, schools and industries. It is now an important issue to save user program and data as well as hardware and software of the personal computer (PC) itself from damage and corruption due to sudden power failure. This paper presents the solution of the problem. A graphical user interface (GUI) has been developed that monitors the status of the power supply of the PC. Whenever power goes out,it saves all the files that are opened and initiates auto-shutdown of the PC.